Comparative public administration is back in, prudently - Jreisat, Jamil E. (2005)
Comparative public administration, in method and in content, has not successfully integrated with the main field of public administration, to the detriment of both. With globalization and changes in information technology, the current separation impairs public administration education. This assessment is based on a literature review and an appraisal of the contributions of comparative scholarship. Suggestions for future research strategies promote viable, integrative, and relevant cross-cultural studies. They emphasize (1) the utilization of cooperative teams of researchers instead of individual efforts; (2) the use of multi-case analysis instead of the traditional single-case approach; (3) improvement of the definition and verification of cultural influences on administration; and (4) expansion of middle-range analysis of examine specific administrative practices across national boundaries as a strategy for enhancing relevance. - Reproduced.
Keywords: Public administration